2020
DOI: 10.3390/biom10030398
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Chromium Picolinate Against Diabetic-Induced Renal Dysfunction and Renal Fibrosis in Streptozotocin-Induced Diabetic Rats

Abstract: Diabetic nephropathy (DN) is one of the most important complications of diabetes, and the leading cause of end-stage renal disease (ESRD). While Chromium picolinate (CrPic) supplementation has been found to be effective in treating diabetes, its effects on diabetic-induced nephropathy have not been studied. Therefore, in this study, CrPic (1 mg kg −1 d −1 ) was administered to a DN rat model by oral gavage for eight weeks to investigate its effects. The results show that CrPic supplementation caused a decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Renal fibrosis is often caused by renal glomerular sclerosis and interstitial fibrosis. Therefore, glomerular visceral epithelial cell development and formation, glomerular filtration, and transfer function act as the internal causes of renal fibrosis ( Qi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Renal fibrosis is often caused by renal glomerular sclerosis and interstitial fibrosis. Therefore, glomerular visceral epithelial cell development and formation, glomerular filtration, and transfer function act as the internal causes of renal fibrosis ( Qi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we observed consistent results in rats challenged with STZ, corroborating the activation of the TGF-β1/Smad2/Smad3 signaling in DN development. The paramount importance of the TGF-β1/Smad signaling has been underscored in various DN pathogenesis, includes podocyte injury, mesangial cell proliferation, and especially renal fibrosis ( Isacsson et al, 1988 ; Tang et al, 2018a , b , 2020 ; Zhang et al, 2019 ; Qi et al, 2020 ). As an important regulator in the pathway, TGF-β1 has been recognized as an effective cytokine that modulates cell proliferation, differentiation, migration, and ECM turnover in the kidney ( Lan and Chung, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of 25 animal studies included in the current systematic review are demonstrated in Table 1. These studies were published between 2006 and 2020 and were from the Asia, 32‐39,42 Africa, 40,41,43,44 Europe, 33,44‐51 and the USA 47,48,52‐54 . Among these 25 animal studies, three studies were conducted on mice, 52,55,56 and 22 studies were conducted on rats 32,33,40‐50,53,54,57‐62 .…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between 2006 and 2020 and were from the Asia, 32‐39,42 Africa, 40,41,43,44 Europe, 33,44‐51 and the USA 47,48,52‐54 . Among these 25 animal studies, three studies were conducted on mice, 52,55,56 and 22 studies were conducted on rats 32,33,40‐50,53,54,57‐62 . Also, among these 25 animal studies, three studies were conducted on animal models of type 1 diabetes, 41,52,55 and 22 studies were conducted on animal models of type 2 diabetes 32,33,40,42‐50,53,54,56‐62 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation